Effects of nano-SiC particles on the FSSW welded AZ31 magnesium alloy joints. Issue 8 (24th May 2017) - Wu, D.; Shen, J.; Lv, L.; Wen, L.; Xie, X.
Abstract : The microstructure of nano-SiC enhancing friction stir spot welding (FSSW) joint with dwell time of 3 s was characterised by an onion ring structure which consisted of alternate SiC-free zones and SiC-rich zones where SiC particles refined the grains. However, onion ring structure disappeared and SiC particles dispersed homogeneously when dwell time was 5 s. The microhardness of stir zone (SZ) and tensile shear load of SiC enhancing FSSW joint were higher than those of conventional FSSW joints. After heat treatment at 200°C for an hour, grains of the SZ grew substantially and coursed reduction in mechanical properties of joints, while grain size of SZ and tensile shear load of SiC enhancing joint was invariant but the microhardness of SZ increased.